2019
DOI: 10.1177/1533317519855154
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Sources Support on Adaptation in Families of Patient With Moderate-to-Severe Dementia in China

Abstract: Purpose: To examine the support from different sources of Chinese families of patients with moderate-to-severe dementia that most heavily influences the family adaptation and the influence pathway. Method: Two hundred and three families participated in this study. Chinese versions of instruments were used. Structural equation modeling was applied to confirm the effect pathway. Results: More family support, kin support, community support, and social support (narrow sense) were related to greater levels of famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…This study found that the average score of family adaptation was 76.00 (SD 18.35), and the average item score was 5.07, which was higher than the theoretical median (60 and 4). This score is consistent with the study by Wang involving patients with Alzheimer's disease ( 31 ). There is currently no cut-off value for this scale.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study found that the average score of family adaptation was 76.00 (SD 18.35), and the average item score was 5.07, which was higher than the theoretical median (60 and 4). This score is consistent with the study by Wang involving patients with Alzheimer's disease ( 31 ). There is currently no cut-off value for this scale.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, perceived support of liver cancer families was measured and divided into inner family support and outer family social support, both of which had direct and indirect effects on family adaptation. The role of support systems in family adjustment has been confirmed in many studies ( 31 , 59 , 60 ). The lack of inner family support networks and outer family social support can lead to family maladjustment.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…To perceive a valuable companionship from care recipient and meaningful relationship with family, kin, or neighbors [17][18][19] Intimacy with cares' recipients and a network of family, kin, or neighbors Religiosity Acceptance the caregiving situation that God had given caregivers 18 Embracing caregiving situation that God sent to caregiver and they cannot avoid Spirituality Finding positive meaning in caregiving situation and mindfulness practice 20,21 Recognition of a positive feeling or sense or belief and peacefulness Self-efficacy Perceived success, role confidence of caregiving, and belief in their own ability 20…”
Section: Social Supportmentioning
confidence: 99%
“…17 Moreover, in several studies, family caregivers gained benefits from social support during their caregiving experiences. 18,19,22,30 Two studies reported that a higher level of social support positively influenced the caregivers' life satisfaction 30 and had an indirect effect on family adaptation to caregiving, ultimately improving caregiver resilience. 22 In Asian countries, informal social support was found to be a major resource for the family caregiver.…”
Section: Social Supportmentioning
confidence: 99%